Estudio de prefactibilidad para la instalación de una planta productora de tabletas efervescentes a base de aguaje (Mauritia flexuosa) - Arrieta Rebaza, Rafael Ricardo (2023)
Women in Peru today are more concerned with personal care and avoiding disease. This due to the disadvantages of having a balanced diet and personal care together with work, family care and daily personal life. In addition, the consumption of vitamin A is essential to be able to have a good physical condition and better personal care. For this reason, we investigated that aguaje is a fruit native to Peru that can satisfy the need for a lack of vitamin A, containing more vitamin than other easily accessible products such as carrots and sweet potatoes. However, the consumption of this fruit is not so common because the fruit is mainly marketed in the jungle of our country. Our product seeks to facilitate the consumption of this fruit for women residing in metropolitan Lima by presenting a product that is easy to access and consume. The plant will be located in the department of San Martín, where access to raw materials will be easy to satisfy the demand for our tablets. We opted to use technology that allows us to eliminate the water in our product, because it reacts when having contact with water. It is estimated that the investment necessary to carry out this project will be 1.8 million soles and that there is a market to sell our product.